Light source position calibration method for photometric stereo in capsule endoscopy. (17th June 2020) - Hao, Yang; Visentini-Scarzanella, Marco; Li, Jing; Zhang, Peisen; Ciuti, Gastone; Dario, Paolo; Huang, Qiang
ABSTRACT: For photometric stereo in capsule endoscopy, calibration of light source is crucial for improving the precision of surface normal estimation. Therefore, this paper presents an improved planar-mirror-based light source position calibration method: from captured images of light source and detected poses of planar mirror, light paths are retraced from camera to light source, and position of light source is triangulated with least square method. The contribution of this paper is that a refraction model of the planar mirror is employed in the retracement of light paths, thus the bias of light paths caused by refraction can be compensated and the position of light source can be estimated more precisely. The results of simulation and experiment show that the proposed method provides higher calibration accuracy than the current planar mirror-based calibration method and can improve the precision of subsequent photometric stereo-based 3D reconstruction. GRAPHICAL ABSTRACT: